2017
DOI: 10.3892/mco.2017.1270
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in the colorectal primary tumor and the synchronous resected liver metastases prior to and after treatment with an anti-EGFR monoclonal antibody

Abstract: Abstract. Molecular heterogeneity between primary tumors (PTs) and synchronous resected liver metastasis in colorectal cancer (CRC) has potential relevance in treatment strategies. Next-generation sequencing (NGS) may be able to increase the chances of identifying multiple molecular driver alterations, calling for therapy. The aim of the present study was to evaluate mutations in PT and synchronous resected liver metastases for patients with Kirsten rat sarcoma 2 viral oncogene homolog (KRAS) exon 2 wild-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Other studies have confirmed the consistent heterogeneity of colorectal cancers at the level of primary tumors and synchronous metastases: this heterogeneity was present before and after anti-EGFR therapy [ 229 ]. Particularly, mutations were observed during therapy loss and the acquisition of KRAS , NRAS , TP53 , PIK3CA , FBXW7 and PTEN [ 230 ].…”
Section: Somatic Genetic Abnormalities In Colon Cancermentioning
confidence: 99%
“…Other studies have confirmed the consistent heterogeneity of colorectal cancers at the level of primary tumors and synchronous metastases: this heterogeneity was present before and after anti-EGFR therapy [ 229 ]. Particularly, mutations were observed during therapy loss and the acquisition of KRAS , NRAS , TP53 , PIK3CA , FBXW7 and PTEN [ 230 ].…”
Section: Somatic Genetic Abnormalities In Colon Cancermentioning
confidence: 99%
“…Yet, another study that was conducted by Li et al (54) demonstrated that miR-223/FBXW7 axis regulates doxorubicin sensitivity through epithelial mesenchymal transition in non-small cell lung cancer. miR-223/FBXW7 pathway has also been investigated for drug resistance in cancers (38,(55)(56)(57). FBXW7 mutation drives acquired resistance to targeted agents cetuximab or panitumumab (58).…”
Section: F-box Proteins and Chemoresistancementioning
confidence: 99%
“…Adua et al analyzed primary tumor and liver metastasis samples from 7 KRAS wild‐type patients and compared the genotypes of 22 genes associated with anti‐EGFR before and after chemotherapy. The results showed marked genotypic differences between pre‐ and post‐treatment samples, which were likely attributable to tumor cell clones selected by therapy . Gong et al analyzed 315 cancer‐related genes and introns of 28 frequently rearranged genes in 138 mCRC cases using FoundationOne.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed marked genotypic differences between pre-and post-treatment samples, which were likely attributable to tumor cell clones selected by therapy. 9 Gong et al analyzed 315 cancer-related genes and introns of 28 frequently rearranged genes in 138 mCRC cases using FoundationOne. They identified a novel KRAS mutation (R68S) associated with an aggressive phenotype.…”
mentioning
confidence: 99%